Cross-cultural analysis of cognitive maps almaty and london residents (The Journal of Psychology and Sociology, 2016)
The structure of an image of the city is always hierarchical. The perception of objects of an urban environment in temporary prospect allows to read out information on the city (its historical past, dominating values, etc.) gradually, organizing it round a basic kernel. Thus, as a rule, the object of an urban environment possessing the maximum weight, the greatest importance for the individual becomes such kernel.All other information on the city, it isn’t dependent on, whether it bears spatial or its social characteristics will be organized round this backbone kernel. After significant objects which in turn are social they caused valuable reference points and at the same time objects of satisfaction of needs of ther ecipient are defined, the greatest weight in its image of the city is got by those objects of an urban environment which at the expense of these or those (most often volume and spatial) characteristics dominate over the others. In recent years in psychology and in a number of interdisciplinary sciences growth of interest to studying of spatial representations of the person is observed. This interest isn’t casual: more and more researchers comes to a conclusion about need of the analysis of informative processes for that appearance which they have in ecologically habitual conditions, in a context of natural purposeful activity. Spatial representations are that phenomenon of an interior which is connected of surrounding space often call cognitive maps. According to opinion of a number of researchers, cognitive maps are among the earliest and strong components of memory having considerable impact on perception, storing and transformation of spatial scenes. U. Naysser believes also what exactly they control our imagination. Task of this article is consideration of results of the researches of spatial representations conducted in recent years at the person. One of results of these researches is opportunity to specify limits of legitimacy of their comparison to topographic maps of the district. In the Soviet psychology, one of the main difficulties lacks of an accurate definition of the following concepts is: spatial orientation; spatial navigation. In the western cognitive psychology there are three basic concepts, describing perception of real space it: cognitive map (cognitive map); spatial navigation and orientation.
Keywords: cognitive map; spatial representations; image of the city; perception of space.